Riscos quimicos em biotério - Carvalho, Paulo Roberto de (2003)
For many professionais who exert its functions in biotery, carrying thorough activities of most diverse, the situations of risk the one that are submitted, are not, for times, very evidenced welt. Then, some questions, in that refers to thr security of these professionais, are urgent and had been boarded in this work, mainly for whom they manipulate, storage and carry chemical substances and operate divere equipament that, if not taken care of the secunty norms, becomes potentially dangerous equiparnent. In truth, when clarified, these professionais they do not display its bodies to the aggressiveness of many you substantiate chemistries, being able, in a future not very distant, to come suffers the consequences to it, that can be fatal, in view of that many of them you substantiate chemistnes act in the long run on the organism. Therefore, this work searched to present the importance of the diagnostic para prevention to the chemical risks to subsidize the workers of biotery of production, creation and experimentation of Iaboratory in the prevention to the occpational chemical risks.